The Emergence of Social Structure: Employer Information Networks in an Experimental Labor Market - Klarita Gerxhani; Jordi Brandts; Arthur Schram (Tinbergen Institute, 2011)
We use laboratory experiments to investigate how employers develop social structures for sharing information about the trustworthiness of job candidates, when worker opportunism is possible. The experimental data show that substantial information sharing emerges. Two types of information networks are observed. One consists of 'anonymity networks' where information is anonymously and voluntarily provided as a collective good for all employers to use. The other type is a 'reciprocity network' where information sharing is driven by the rewarding of previously given information by the requestor. In both types, the extent of information sharing depends on the costs of providing it. Moreover, information sharing enables employers to recruit trustworthy workers which creates a high quality of trading, benefiting both employer and worker.
Keywords: Z13; J23; 330; Social structure; Information networks; Recruitment; Experiments; Personalbeschaffung; Soziales Netzwerk; Informationsverbreitung; Test; Amsterdam